PENGUJIAN BEBERAPA VARIETAS KEDELAI (Glycine max L.) PADA KONDISI CEKAMAN KEKERINGAN - Ardian, Ardian; Deviona, Deviona; Nathisa, Dina (Fakultas Pertanian, Universitas Janabadra, 2024)
Soybean (Glycine max L.) is one of the main food crop commodities in Indonesia which ranks third after rice and corn. The need for soybeans from year to year continues to increase, while domestic soybean production is unable to meet so that Indonesia must import soybeans. Efforts to reduce dependence on soybean imports can be made by increasing domestic soybean production. Increased soybean production is often less successful if faced with land conditions that experience stress, especially drought stress. The use of soybean varieties that are resistant to drought stress is needed to prevent the risk of yield reduction due to drought. This research was conducted using a 2-factor factorial completely randomized design (CRD). The first factor is the volume of water application, consisting of 4 levels: 100% water requirement, 80% water requirement, 70% water requirement, and 60% water requirement. The second factor is soybean genotype, consisting of 3 levels, namely: The parameters observed were: plant height, flowering age, harvesting age, root length, root dry weight, crown dry weight, root crown ratio, total number of pods per plant, number of pods, number of seeds per plant, and seed weight per plant. The research data were analyzed by analysis of variance and continued with Duncan's multiple range test at the 5% level. The results showed that the soybean variety Dering 3 can be recommended as a drought tolerant variety based on several parameters observed (plant height, flowering age, number of pods per plant, number of pods per plant, number of seeds per plant, seed weight per plant). Keywords: Growth, Yield, Soybean, Drought Tolerant INTISARIKedelai (Glycine max L.) merupakan salah satu komoditas tanaman pangan utama di Indonesia yang menempati urutan ketiga setelah padi dan jagung. Kebutuhan kedelai dari tahun ke tahun terus meningkat, sedangkan produksi kedelai dalam negeri tidak mampu memenuhi sehingga Indonesia harus impor kedelai. Upaya dalam mengurangi ketergantungan terhadap impor kedelai dapat dilakukan dengan meningkatkan produksi kedelai dalam negeri. Peningkatan produksi kedelai seringkali kurang berhasil jika dihadapkan pada kondisi lahan yang mengalami cekaman, khususnya cekaman kekeringan. Penggunaan varietas kedelai yang tahan terhadap cekaman kekeringan diperlukan untuk mencegah resiko penurunan hasil akibat kekeringan. Penelitian ini dilakukan dengan menggunkan Rancangan Acak Lengkap (RAL) faktorial 2 faktor. Faktor pertama volume pemberian air, terdiri dari 4 taraf yaitu: kebutuhan air 100%, kebutuhan air 80%, kebutuhan air 70%, dan kebutuhan air 60%. Faktor kedua adalah genotipe kedelai, terdiri dari 3 taraf yaitu: varietas Devon 1, varietas Deja 1 dan varietas Dering 3. Parameter yang diamati yaitu: tinggi tanaman, umur berbunga, umur panen, panjang akar, berat kering akar, berat kering tajuk, rasio tajuk akar, jumlah polong total per tanaman, jumlah polong bernas, jumlah biji per tanaman, dan berat biji per tanaman. Data hasil penelitian dianalisis dengan analisis ragam dan dilanjutkan dengan uji jarak berganda Duncan pada taraf 5%. Hasill penelitian menunjukkan bahwal varietas kedelai Dering 3 dapat direkomendasikan sebagai varietas toleran kekeringan berdasarkan beberapa parameter yang diamati (tinggi tanaman, umur berbunga, jumlah polong per tanaman, jumlah polong bernas per tanaman, jumlah biji per tanaman, berat biji per tanaman). Kata Kunci: Pertumbuhan, lHasil, Kedelai, Cekaman